2014
DOI: 10.1097/wnf.0000000000000039
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype Analysis of GSK-3β Gene Polymorphisms in Bipolar Disorder Lithium Responders and Nonresponders

Abstract: The GSK-3β gene, GSK3B, codes for an enzyme that is a target for the action of mood stabilizers, lithium and possibly valproic acid.In this study, the relationship between haplotypes consisting of single nucleotide polymorphisms (SNPs) of GSK3B −50T/C and −1727A/T and the effect of lithium was studied among Japanese bipolar disorder lithium nonresponders and responders.The distributions of the GSK3B haplotypes (−50T/C and −1727A/T) showed a trend for significant difference between the lithium nonresponders and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…In the search for new drug targets, glycogen synthase 3 (GSK-3) has taken center stage for its known involvement in several pathways linked to both BD and diabetes mellitus (Gould et al 2004 ; Ronai et al 2014 ; Huang et al 2014 ; Iwahashi et al 2014 ). In the rat, lithium, a standard treatment for BD, reduces the enzyme’s activity in the hippocampus and improves memory and learning (Qu et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the search for new drug targets, glycogen synthase 3 (GSK-3) has taken center stage for its known involvement in several pathways linked to both BD and diabetes mellitus (Gould et al 2004 ; Ronai et al 2014 ; Huang et al 2014 ; Iwahashi et al 2014 ). In the rat, lithium, a standard treatment for BD, reduces the enzyme’s activity in the hippocampus and improves memory and learning (Qu et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lithium is considered to influence numerous neuroprotective pathways through increasing phosphorylated GSK3β and inhibiting its action, ameliorating the effects of excitotoxicity [ 82 ]. Previous studies have reported treatment response to lithium to be predicted by GSK3β gene expression and phosphorylation [ 83 , 84 ], and lithium induced increases in phosphorylated GSK3β to be correlated with symptom improvement [ 82 ]. Brain-derived neurotrophic factor (BDNF) is well known for its involvement in neuronal maturation, differentiation and survival, synaptic plasticity, and long-term memory consolidation, and is highly expressed in the cerebral cortex and hippocampus [ 85 ].…”
Section: Therapeutic Mechanisms Of Lithiummentioning
confidence: 99%
“…By comparing Tables 2 , 3 one can see that the genes GSK3β , BDNF , and SLC6A4 (serotonin transporter) seem to be involved bilaterally in poor and good response to lithium in different studies. Some of these studies showed no significant association with lithium response for the following gene variants: BDNF gene, G196A/Val66Met ( Masui et al, 2006 ; Michelon et al, 2006 ; Wang et al, 2014 ) and rs10835210, rs11030101, rs11030102, rs12273363, rs2030324, rs2049045, rs6265”, rs7103411, rs962369, and rs988748 ( Drago et al, 2010 ); SLC6A4 gene, s/s, s/l, and l/l ( Serretti et al, 2004 ; Masoliver et al, 2006 ; Michelon et al, 2006 ; Manchia et al, 2009 ); and GSK3β gene, rs3755557 (-1727A/T) ( Michelon et al, 2006 ; Numajiri et al, 2012 ; Iwahashi et al, 2014 ), rs334558 (-50T/C) ( Szczepankiewicz et al, 2006 ; Iwahashi et al, 2014 ), and rs11921360-A ( Mitjans et al, 2015 ). On the other hand, other studies did find an association of the following variants of GSK3β , BDNF , and SLC6A4 with lithium response in patients with BD: GSK3β gene, rs334558 (−50T/C) ( Adli et al, 2007 ; Benedetti et al, 2012 ; Numajiri et al, 2012 ; Lin et al, 2013 ; Mitjans et al, 2015 , 3), rs6438552 ( McCarthy et al, 2011 ), rs3755557 (-1727A/T) ( Iwahashi et al, 2014 ), rs1732170-rs1192136 ( Mitjans et al, 2015 ); BDNF gene, Val66Met rs6265 ( Rybakowski et al, 2005 ; Dmitrzak-Weglarz et al, 2008 ; Rybakowski et al, 2012 ; Wang et al, 2012 ; Wang et al, 2014 ) and rs988748 ( Dmitrzak-Weglarz et al, 2008 ); and SLC6A4 gene, l/l and s/s ( Serretti et al, 2001 ; Benedetti et al, 2012 ), s allele and 10 repeat allele of STin2 (STin2.10) ( Tharoor et al, 2013 ), and ins/del 44 pz ( Rybakowski et al, 2012 ).…”
Section: Pharmacogenetic Studies In Bipolar Disordermentioning
confidence: 99%